Heterozygous Embryonic Stem Cell Lines Derived from Nonhuman Primate Parthenotes - Dighe, Vikas; Clepper, Lisa; Pedersen, Darlene; Byrne, James; Ferguson, Betsy; Gokhale, Sumita; Penedo, M. Cecilia T.; Wolf, Don; Mitalipov, Shoukhrat (Stem cells (Dayton, Ohio), 2008)
Monoparental parthenotes represent a potential source of histocompatible stem cells that should be isogenic with the oocyte donor and therefore suitable for use in cell or tissue replacement therapy. We generated five rhesus monkey parthenogenetic embryonic stem cell (PESC) lines with stable, diploid female karyotypes that were morphologically indistinguishable from biparental controls, expressed key pluripotent markers, and generated cell derivatives representative of all three germ layers following in vivo and in vitro differentiation. Interestingly, high levels of heterozygosity were observed at the majority of loci that were polymorphic in the oocyte donors. Some PESC lines were also heterozygous in the major histocompatibility complex region, carrying haplotypes identical to those of the egg donor females. Expression analysis revealed transcripts from some imprinted genes that are normally expressed from only the paternal allele. These results indicate that limitations accompanying the potential use of PESC‐derived phenotypes in regenerative medicine, including aberrant genomic imprinting and high levels of homozygosity, are cell line‐dependent and not always present. PESC lines were derived in high enough yields to be practicable, and their derivatives are suitable for autologous transplantation into oocyte donors or could be used to establish a bank of histocompatible cell lines for a broad spectrum of patients. Disclosure of potential conflicts of interest is found at the end of this article.